Optimizing Power System Performance: The Significance of Placement and Sizing of Battery Energy Storage Systems - Harith B. Hussien; Ahmed J. Abid; Naseer M. Yasin; Ameer L. Saleh; Hayder Jasim Habil (Journal of Techniques)
The Battery Energy Storage System (BESS) has become a key tool for improving power system performance. However, the use of BESS in a distribution grid has several problems including deciding where to position it and how much capacity should be used to maximize its benefits. The purpose of this study is to optimize the siting and sizing of BESS for enhanced voltage profile and reduced power losses across the distribution system. To do this, two meta-heuristic optimization algorithms are suggested in this paper, Particle Swarm Optimization (PSO) and Dragonfly Algorithm (DA). Two cases have been presented. The first case includes 33 buses, while the second has 85 buses. The results of both cases are successfully effective in reducing system losses and improving the voltage profiles in power systems. It is observed that losses reduce by 45.59% compared to the base case for Case 1. The value in Case 2 decreases by 40.09% compared to the base case. The voltage profiles in Case 1 show an increase, with a minimum voltage of 0.95 PU, compared to the base case where the minimum voltage was at 0.904 PU. In Case 2, the minimum voltage becomes 0.95 PU instead of 0.874 PU in the base case.